Digital (Dis)connection, Agency, and Imagination in a French Rural Community - Fabienne Darling-Wolf (Social Media + Society)
Common to scholarly analyses of the “digital revolution” is their inclination to deploy technology—the platforms, their affordances, the virtual spaces they create—as the main entry into evaluations of digital media’s impact on socio-cultural organization. While certainly useful in helping us understand the dynamics of digital practices and spaces, these narratives often fail to provide a fuller portrait of individuals’ broader relationship to the technological world shaped not (only) by their digital media use (or lack thereof) but also by their mere awareness of the existence of digital tools. Drawing from 14 months of ethnographic fieldwork in as small rural community in France, this project starts sketching such a portrait. Inspired by theories of mediation that encourage us to “rediscover” people as a methodological starting point by moving our focus from object (media) to process (mediation), it explores how residents experience, enjoy, resist, and negotiate the impact of digital and social media on the community’s culture, identity, and social organization.